2006
DOI: 10.1038/sj.jcbfm.9600305
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Complement C3 in Intracerebral Hemorrhage-Induced Brain Injury

Abstract: Activation of the complement cascade contributes to brain injury after intracerebral hemorrhage (ICH). However, a recent study found that complement C5 deficient mice had enhanced ICH-induced brain injury. The present study, therefore, investigated the role of complement C3 (which is upstream from C5) in ICH. Male complement C3 deficient and sufficient mice had an intracerebral infusion of 30-lL autologous whole blood. The mice were killed and the brains were sampled for edema, Western blotting, immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 34 publications
3
66
0
3
Order By: Relevance
“…Application of N-acetylhepain, an inhibitor of complement activation, suppressed edema formation (42). Moreover, C3-deficient mice that underwent autologous blood injection exhibited less brain edema, lower HO-1 levels, less microglia activation, and neutrophil infiltration, concomitantly with alleviated deficits in motor functions, compared to wild-type mice (43). The deleterious role of C3 is also supported by a study using a C3a-receptor antagonist.…”
Section: Complementsupporting
confidence: 48%
“…Application of N-acetylhepain, an inhibitor of complement activation, suppressed edema formation (42). Moreover, C3-deficient mice that underwent autologous blood injection exhibited less brain edema, lower HO-1 levels, less microglia activation, and neutrophil infiltration, concomitantly with alleviated deficits in motor functions, compared to wild-type mice (43). The deleterious role of C3 is also supported by a study using a C3a-receptor antagonist.…”
Section: Complementsupporting
confidence: 48%
“…Very few studies have evaluated adipokines in relation to ICH although C3 has been implicated in ICH pathogenesis [23,13,10]. We did see differences in the %ASP/C3, ASP, and C3 but not adiponectin, as has been shown with ICH and stroke in a previous study [24].…”
Section: Discussionsupporting
confidence: 59%
“…By contrast, Chen et al found that a BMI below 20 was also a risk for factor ischemic heart disease in the Chinese population [2]. Hypertension, which is prevalent in the Chinese population, is another major risk factor for both ICH and MI [10,8]. Taken together, these risk factors may be responsible for the higher rates of cardiovascular diseases (CVD) and the development of CVD at a young age in Chinese individuals [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, C1q, C3, and other complement components contributed to brain edema and histopathology in models of ischemic and hemorrhagic brain injury (Ten et al, 2005;Yang et al, 2006). In a closed head TBI model, Rancan et al (2003) reported that astrocyte overexpression of soluble complement receptor protein y (sCrry), a mouse-specific C3 convertase inhibitor, reduced posttraumatic bloodbrain barrier damage and improved neurologic severity scores (including motor function, alertness, and physiologic behavior).…”
Section: Discussionmentioning
confidence: 99%